The Effect of Using Taboo Game on Vocabulary Mastery of Senior High School Students - Ahmad Gilang Caraka (My University, 2025)
Vocabulary mastery is a crucial foundation in learning English, but it is often a challenge for high school students in Indonesia. Traditional methods such as translating books are often considered boring and less effective in promoting long-term retention and active use. Therefore, a more interactive, fun, and contextual learning approach is needed. Educational games such as Taboo Game, where players must describe target words without using certain "taboo" words, offer the potential to increase student engagement and force them to actively access and use synonyms, antonyms, and descriptions. This research aims to test the effectiveness of Taboo Game as a vocabulary learning tool in the context of formal high school education. This research used a quasi-experimental design with a non-equivalent control group. It was conducted at senior high school located at Rambipuji. The participant consisted of two classes from tenth-grade students. One class designated as the experimental group receiving vocabulary learning using the Taboo Game, while the other class served as the control group taught using the traditional method. Both groups were given an equivalent vocabulary post-test after the treatment to measure improvement. The treatment was carried out for 2 meetings for each class, with the topic of personality vocabulary according to the curriculum. The data collection instrument is a multiple-choice vocabulary test. Data were analyzed quantitatively using an independent t-test to compare the average scores of improvements between the two groups. The results showed that the control group had a mean score of 60.43 while the experimental group scored an average of 72.35. The significance value (2 tailed) was 0.03, which is lower than 0.05, indicating a statistically significant difference. These results reveal that students who participated in Taboo Game activities demonstrated significantly greater effect in vocabulary mastery compared to those who received conventional instruction. This suggests that the Taboo Game is an effective tool for enhancing vocabulary mastery of senior high school students. This research was expected to the English teachers to integrate the Taboo game into their vocabulary learning as an interactive and engaging learning tool. For the future researhers, this research was expected to explore the long-term effects of using the Taboo Game on vocabulary mastery.
Reaploud Repository February_agus
Keywords: Influence; Taboo Games; Mastery; Vocabulary